THE MAIN PROBLEMS IN TEACHING ENGLISH TO PRESCHOOL CHILDREN - Gʻaniyeva Xayriniso; Boboyeva Sarvinoz (Journal of new century innovations, 2023)
Annotation: This article describes the importance and role of teaching English in our society today. It also discusses the importance of teaching English to children of preschool age and the difficulties and problems that arise in this process and their solutions.